2013
DOI: 10.1590/s0102-311x2013001100018
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with alcohol intake and alcohol abuse among women in Belo Horizonte, Minas Gerais State, Brazil

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…That is, these substances are more connected to social isolation and mental suffering behaviors. Studies point out that individuals tend to use psychosocial substances to deal with stress, tensions and mental suffering situations 4,30 , showing the importance of approaching themes related to mental suffering during childhood.…”
Section: Discussionmentioning
confidence: 99%
“…That is, these substances are more connected to social isolation and mental suffering behaviors. Studies point out that individuals tend to use psychosocial substances to deal with stress, tensions and mental suffering situations 4,30 , showing the importance of approaching themes related to mental suffering during childhood.…”
Section: Discussionmentioning
confidence: 99%
“…(2)(3)(4) According to the Brazilian National Transplant Registry, in June 2013 there were 22,187 patients registered on the waiting list for solid organ transplantation of these, 19,913 (89.75%) were waiting for a kidney. (5) Kidney transplantation requires compatibility between tissues obtained for the Human Leukocyte Antigen typing (HLA). While waiting for a donor, the chronic renal disease patients have other forms of Renal Replacement Therapy (RRT) allow the maintenance of their life and also justify the increasing number of patients registered on the waiting list for a kidney transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Although most of the study participants present preservation of mobility and functionality for the most part, we noted the presence of pain complaints, especially in the lower limbs. Pain in lower limbs are more frequent, and can be explained by the significant physical inactivity found among these patients, but also by the late uremic consequences on the muscular, metabolic, circulatory and skeletal systems, which cause symptoms such as early fatigue, peripheral circulatory deficit, changes sensitivity, muscle dysfunction and peripheral neuropathy 3,4,10,11,16 . Physical inactivity was high among our transplanted patients, similar to those found in the study by Costa, Nogueira 16 , which reported a frequency of 66.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic Kidney Disease (CKD) is considered an important public health problem with high prevalence, morbimortality rate and cost of treatment 1,2,3 . Once installed the CKD requires substitutive kidney treatment at the disease's final stage 3,4,5 .Among the therapeutic modalities to be established for these patients, the kidney transplant represents the most durable treatment with benefits in the survival, quality of life and in the cost-effectiveness, when compared to dialysis, forming the gold treatment for the disease's final stage 6,7,8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation